Non-Invasive Ventilation in Patients with Heart Failure: A Systematic Review and Meta-Analysis - Hugo Souza Bittencourt (Arquivos Brasileiros de Cardiologia)
Abstract Non-invasive ventilation (NIV) may perfect respiratory and cardiac performance in patients with heart failure (HF). The objective of the study to establish, through systematic review and meta-analysis, NIV influence on functional capacity of HF patients. A systematic review with meta-analysis of randomized studies was carried out through research of databases of Cochrane Library, SciELO, Pubmed and PEDro, using the key-words: heart failure, non-invasive ventilation, exercise tolerance; and the free terms: bi-level positive airway pressure (BIPAP), continuous positive airway pressure (CPAP), and functional capacity (terms were searched for in English and Portuguese) using the Boolean operators AND and OR. Methodological quality was ensured through PEDro scale. Weighted averages and a 95% confidence interval (CI) were calculated. The meta-analysis was done thorugh the software Review Manager, version 5.3 (Cochrane Collaboration). Four randomized clinical trials were included. Individual studies suggest NIV improved functional capacity. NIV resulted in improvement in the distance of the six-minute walk test (6MWT) (68.7m 95%CI: 52.6 to 84.9) in comparison to the control group. We conclude that the NIV is an intervention that promotes important effects in the improvement of functional capacity of HF patients. However, there is a gap in literature on which are the most adequate parameters for the application of this technique.